2000
DOI: 10.1038/82153
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to diet-induced hypercholesterolemia and gallstone formation in ACAT2-deficient mice

Abstract: The importance of cholesterol ester synthesis by acyl CoA:cholesterol acyltransferase (ACAT) enzymes in intestinal and hepatic cholesterol metabolism has been unclear. We now demonstrate that ACAT2 is the major ACAT in mouse small intestine and liver, and suggest that ACAT2 deficiency has profound effects on cholesterol metabolism in mice fed a cholesterol-rich diet, including complete resistance to diet-induced hypercholesterolemia and cholesterol gallstone formation. The underlying mechanism involves the lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
268
2
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(292 citation statements)
references
References 35 publications
20
268
2
2
Order By: Relevance
“…It is the predominant enzyme responsible for the synthesis of cholesterol esters and their subsequent secretion with lipoproteins. ACAT2 deficiency results in a considerable decrease in the rate of cholesterol absorption (26). The rate of cholesterol esterification in the presence of these enzymes is notably enhanced by substrate availability, but, as we demonstrated recently, it is inhibited by product accumulation.…”
Section: Cholesterolmentioning
confidence: 73%
See 1 more Smart Citation
“…It is the predominant enzyme responsible for the synthesis of cholesterol esters and their subsequent secretion with lipoproteins. ACAT2 deficiency results in a considerable decrease in the rate of cholesterol absorption (26). The rate of cholesterol esterification in the presence of these enzymes is notably enhanced by substrate availability, but, as we demonstrated recently, it is inhibited by product accumulation.…”
Section: Cholesterolmentioning
confidence: 73%
“…DGAT1, which is expressed in several tissues (including liver, intestine, and skin), differs from DGAT2 in that defective fat absorption is not seen in DGAT1-KO mice. In recent studies, investigators have found that MGAT2 (29,31) and MGAT3 (30) possess DGAT activity (26,170). Some TAG synthesis also occurs through the dephosphorylation of phosphatidic acid and acylation of the resultant DAG.…”
Section: Triacylglyceridesmentioning
confidence: 99%
“…As inferred from our cumulative results, it is highly probable that lack of APO-B48 expression induces the inhibition of intestinal absorption and hepatic bioavailability, which results in contributing considerably less cholesterol to biliary secretion. Studies that underline the importance of chylomicron remnant cholesterol in murine cholelithogenesis are that disturbed hepatic uptake of chylomicron remnants in APO-E-deficient mice 40 and impaired intestinal cholesterol esterification in acyl-CoA: cholesterol acyltransferase 2 knockout mice 41 significantly reduce biliary cholesterol secretion and gallstone formation. More recently, we found that biliary secretion of chylomicron remnant cholesterol is more rapid in gallstone-susceptible C57L mice than in gallstone-resistant AKR mice.…”
Section: Discussionmentioning
confidence: 99%
“…The Acat1 −/ − and Acat2 −/− mice (53,54) in C57BL/6 background were received from Sergio Fazio (Nashville, TN) and Shailesh Patel (Charleston, SC), respectively. The 3XTg-AD mice (AD mice) in hybrid 129/C57BL/6 background contain two mutant human transgenes, hAPP harboring Swedish mutation (hAPPswe), and mutant htau (htau P301L ), and contain the knock-in mutant presenilin 1 (PS1 M146V ) (55).…”
Section: Methodsmentioning
confidence: 99%